Analisis Efisiensi Rantai Pasok Sayuran Hortikultura Pada Asosiasi Aspakusa Makmur Boyolali: Analisis Efisiensi Rantai Pasok Sayuran Hortikultura Pada Asosiasi Aspakusa Makmur Boyolali - Zainul Muttaqin; Retna Dewi Lestari; Setyo Rahyunanto (Journal Science Innovation and Technology (SINTECH), 2026)
This study aims to determine the efficiency value of the vegetable product supply chain in the Aspakusa Makmur Boyolali Association. Aspakusa Makmur Boyolali is a fresh vegetable distributor company that distributes channels from partner farmers to retail supermarkets such as Lotte Mart, Superindo, and other retailers in the Central Java Region. The analysis method used in this study is Data Envelopment Analysis (DEA) and uses DMU (Decision Making Unit), this method is a mixture of quantitative and qualitative methods. The results of the study show that the distribution of vegetables from farmers to Aspakusa and to Retail is inefficient due to several factors. Factors affecting inefficiencies include limited access to technology, fluctuations in market demand, and supply instability due to weather. These findings confirm the need to increase production capacity, adopt modern technology, and strengthen distribution networks to improve supply chain efficiency in Aspakusa Makmur Boyolali. To increase efficiency, strategic efforts are needed in the form of increasing production capacity, using modern agricultural technology, and strengthening distribution and institutional networks. The results of the research are expected to be a reference for relevant institutions in formulating policies to strengthen the horticultural supply chain at the local and regional levels.